A proposed conceptualization of talent in sport: The first step in a long and winding road - Baker, J.; Wattie, N.; Schorer, J. (Psychology of Sport and Exercise, 2019)
Objectives: The validity of sporting talent is hotly contested by those working, watching, and participating in sport in its variety of forms. Despite considerable research attention to understanding talent development in sport settings, the overall utility of this concept is not known. One of the reasons for this is that sporting talent has not been adequately conceptualized. This paper aims to provide a broad foundation for exploring talent in sport. Design: Critical review. Methods: Prior work from psychology, sport psychology and sport science more generally are reviewed to develop a new conceptualization of talent in sport. Results and conclusions: We propose a multi-faceted conceptualization of talent as: innate (i.e., originating in biological elements present at birth), multi-dimensional (i.e., consisting of capacities from a range of broad cognitive, physical, and psychological categories), emergenic (i.e., involving interactions among factors that combine multiplicatively), dynamic (i.e., evolving across developmental time due to interactions with environments and random gene expression) and symbiotic (i.e., cultural and social factors will determine the ultimate value of an individual`s talent). We also suggest several avenues for future research to determine the validity of talent in sport.